Review of Strategic Branding and Consumer Perceptions of Indian Companies for Brand Equity (International Journal of Food and Nutritional Sciences, 2022)
This study explores strategic branding initiatives and their impact on brand equity in the context of Indian companies. It investigates consumer perceptions and the factors influencing brand equity, focusing on strategies employed by companies to enhance brand value and customer loyalty. Utilizing qualitative and quantitative methods, the research examines case studies and consumer surveys to analyze how branding strategies shape consumer perceptions and influence brand equity. Findings highlight the importance of authenticity, consistency, and customer engagement in building strong brand equity. The study contributes to understanding effective branding practices in diverse market environments, providing insights for marketers and strategists aiming to strengthen brand positioning and consumer relationships in the competitive Indian market landscape.